2014
DOI: 10.1111/1471-0528.12837
|View full text |Cite
|
Sign up to set email alerts
|

Maternal depression from early pregnancy to 4 years postpartum in a prospective pregnancy cohort study: implications for primary health care

Abstract: Objective To describe the prevalence of maternal depression from pregnancy to 4 years postpartum, and the risk factors for depressive symptoms at 4 years postpartum.Design Prospective pregnancy cohort study of nulliparous women.Setting Melbourne, Australia.Sample In all, 1507 women completed baseline data in pregnancy (mean gestation 15 weeks).Methods Women were recruited from six public hospitals. Questionnaires were completed at recruitment and 3, 6, 12 and 18 months postpartum, and 4 years postpartum.Main o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(119 citation statements)
references
References 35 publications
3
112
2
2
Order By: Relevance
“…These studies rely on self-reported symptoms (Lacoursiere et al, 2006) or they used different screening tools (the Edinburgh Postnatal Depression Scale, LaCoursiere et al, 2010 or the CES-D Carter et al, 2000) but none of these studies examined the association beyond 14 months after delivery. Woolhouse et al (2014) examined the point prevalence of maternal depression repeatedly from three months postpartum till four years postpartum. Their findings suggest, unexpectedly, that the risk of depression was highest four years after delivery, indicating a need for long follow-up periods when studying maternal depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies rely on self-reported symptoms (Lacoursiere et al, 2006) or they used different screening tools (the Edinburgh Postnatal Depression Scale, LaCoursiere et al, 2010 or the CES-D Carter et al, 2000) but none of these studies examined the association beyond 14 months after delivery. Woolhouse et al (2014) examined the point prevalence of maternal depression repeatedly from three months postpartum till four years postpartum. Their findings suggest, unexpectedly, that the risk of depression was highest four years after delivery, indicating a need for long follow-up periods when studying maternal depression.…”
Section: Discussionmentioning
confidence: 99%
“…Early motherhood is a psychological challenge for most women (Woolhouse et al, 2014), and pregnancy and the first months after delivery are generally considered periods of high risk for depression (Thombs et al, 2014). Depression has been labelled a leading cause of disability among women (Kessler, 2003;Konttinen et al, 2013;Thombs et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, most initial data collection was conducted 10 to 20 years ago and there is need for contemporary data on this topic. With the exception of the work by Woolhouse et al (2014), none of these studies included depressive symptoms occurring in pregnancy, even though these are prevalent (12.4%) and associated with risk of later depression (Banti et al 2011;Gaillard et al 2014;Vliegen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…What this finding may also suggest is that other women who did not report mental health impairment in pregnancy went on to experience mental health impairment in the years following their baby's birth. Overall, this observed increase in the proportion of women with mental health impairment at 21 years was not unexpected, as other findings have reported similar increases in the proportion of women with depression, over studies of four years (Woolhouse et al, 2015) and 12 years (Agnafors et al, 2013). While, having poor mental health in pregnancy proved to be one of the strongest predictors of maternal poor mental health over time, other contributing factors reported in this thesis' findings, such as women's socio-demographic and lifestyle characteristics and other factors, no doubt influence the mental health of this latter group of women.…”
Section: Proportions and Patterns Of Women's Mental Health Impairmentsupporting
confidence: 83%
“…One longitudinal study found the proportion of women with Edinburgh Postnatal Depression Scale (EPDS) cut-offs for depression at three months postnatal was 6.9% and at four years post birth the proportion had increased to 14.5% (Woolhouse et al, 2015). Another study found the prevalence of depression in a sample of women was 10.4% at three months post birth and increased to 18.2% at 12 years post birth (Agnafors et al, 2013).…”
Section: Prevalence and Trajectories Of Poor Mental Health Over Timementioning
confidence: 99%